Traffic light nutrition labeling policy: a path to promoting healthier eating habits in Pakistan - Ghauri, Kinza Habib (Journal of the Pakistan Medical Association, 2024)
Dear Editor, While the global burden of diet-related diseases continues to escalate1, it is disheartening to see that Pakistan, like many other Lower-Middle Income Countries (LMICs)2, has not yet ultimately adopted the system that can significantly assist consumers in making healthier food decisions. In Pakistan, the prevalence of obesity, diabetes, and other non-communicable disease conditions is on the rise, posing a substantial economic and health burden on individuals and the healthcare system2. Many countries like the United States, Australia, and the United Kingdom use the traffic light nutrition labeling system, which is a valuable tool for empowering consumers to make informed food choices quickly 3. It provides a simple way for people to quickly assess the nutritional value of a product using a color-coding system3. Green labels indicate healthier options, amber labels suggest moderate consumption and red labels highlight food that should be consumed sparingly4. The simple color-coding system empowers consumers to make healthier decisions and can contribute to a reduction in diet-related diseases4. The traffic light system works particularly well in settings with high illiteracy rates, as is prevalent in Pakistan since it relies on simple color coding rather than textual information5. As consumers, we lack a clear and uniform method for evaluating the nutritional components of the food we buy. This deficiency not only obstructs the capacity to make healthy food choices but also sustains the prevalence of diet-related issues. Color-coded labeling would help people with low literacy levels to understand the nutrition information available on food products easily. However, Traffic Light nutrition labelling has not been adopted in Pakistan. To confront this challenge, policymakers, health organizations, and government authorities should take swift and decisive action. The government must take the lead in implementing clear regulations that mandate the use of traffic light nutrition labels on packaged food items. These regulations should accompany strict enforcement measures. Launching public awareness campaigns about the benefits of the traffic light system can help familiarize consumers with this approach and generate demand for healthier food products. Collaboration and engagement with food manufacturers and retailers to ensure a smooth transition to the traffic light system is imperative to encourage the production of healthier food consumption. Implement a system of periodic reviews and updates of the labeling system to ensure its collective effectiveness and relevance to the evolving nutritional landscape. ---Continue